Consumer trust and confidence: Some recent ideas in the literature - Fife-Schaw, C.; Barnett, J.; Chenoweth, J.; Morrison, Greg; Lundéhn, C. (2008)
This paper reflects on two recent debates in the consumer literature on trust that have implications for consumer relations in the water industry. The first concerns an important yet seldom made distinction between trust and confidence. The second concerns when and how trust is related to acceptance of, for example, new tariffs or new technologies, and it challenges the conventional view that trust is usually a precursor of acceptance. New conceptual models addressing these debates are described and their implications for future water-related consumer research are discussed as are potential implications for industry relationships with consumers. © IWA Publishing 2008.